(untitled) (Fiep Bulletin - online, 2014)
Autism is a pervasive developmental disorder defined by the presence of abnormal development and / or compromised in all three areas of social interaction, communication and restricted and repetitive behavior. Manifests itself before the age of three. The practice of swimming has provided means for stimulating the development of sensory and psychomotor phase in which they are children diagnosed with (TEA), reflecting directly on the general quality of life of these individuals. Objective: To evaluate the relevance of the practice of swimming and its benefits for improving the quality of life of autistic. Material and Method: The study population consisted of 26 children of 3-8 years old, all were diagnosed with the disorder , with 14 practitioners of swimming lessons ( Patient Group ) with a frequency of twice a week during the period of (30 months) and 12 children did not practice ( control group ) . This period were used as parameters for monitoring, filming, comparisons of anamnesis and functional - emotional every 3 months through Data Base testing. Conclusion : It was found that the practice of swimming for this audience in particular , has contributed to , affective and psychomotor social development , with strong acceptance , with the aim of improving the overall quality of life of individuals with the disorder involved in the study , giving support resolutions of the common problem situations in their daily lives Swimming, autism, quality of life